Honokiol Inhibits Proliferation, Invasion and Induces Apoptosis Through Targeting Lyn Kinase in Human Lung Adenocarcinoma Cells - Dai, Xi; Li, Run-Ze; Jiang, Ze-Bo; Wei, Chun-Li; Luo, Lian-Xiang; Yao, Xiao-Jun; Li, Guo-Ping; Leung, Elaine L.-H. (Frontiers in Pharmacology, 2018)
Abstract Honokiol is a natural compound with small molecular structure and extracted from bark of magnolia trees. The biological activities of honokiol includes anti-oxidation, anti-inflammation as well as anti-tumor. However, their mechanism remains unknown. In this study, A549 cell line and EGFR-mutant cell line PC-9 with higher expression level of Lyn than A549 cells were used to assess the anti-tumor effects of honokiol. As shown in this study, honokiol is an effective drug on inhibiting proliferation and inducing apoptosis depended on Lyn and EGFR signal pathway regulated by Lyn, and its efficacy is stronger in PC-9 cells than A549 cells. In addition, this anti-tumor effect in PC-9 cells was weakened by Lyn-knockdown. Taken together, this study indicated the mechanism of honokiol on lung adenocarcinoma and provide a possibility of honokiol as an effective anti-tumor medicine.